DEVELOPMENT OF SMARTPHONE-BASED INTERACTIVE E-BOOK MULTIMEDIA FOR LEARNING TECHNICAL DRAWING IN VOCATIONAL SCHOOLS - Tuah; Danar Ariangga Windra Gautama; Mega Kurniawatie (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
This study aims to develop a Smartphone-Based Iteractive Multimedia e-Book of the draw lines learning and provide an alternative instructional media that can be used by students. This study is categorized as research and development Borg & Gall model. The assessment results were obtained through the responses of 50 grade X vocational school students to interactive multimedia e-Books by conducting product usability tests, that have reached criteria “very good”. The results of this research was a product in the form of a smartphone-based interactive multimedia e-Books of the draw lines learning. E-Books also has an impact on student understanding that shown by the value of Gain with category “medium”. Therefore, e-Books can be used as an alternative instriuctional media that is feasible for students and teachers.